(untitled) (Research, Society and Development, 2022)
Nursing occupies a prominent place in health, both nationally and internationally. The professional nurse has decision-making skills and is proactive, with regard to recognizing the needs of care and attention and protection of society, as well as promoting the population’s health in its various aspects. This article aims to describe the importance of nursing work on the front line against COVID-19, outlining the risks and challenges faced by nurses in the face of the pandemic. This is an integrative literature review, with data searches carried out in the following databases: Scielo, Lilacs (DECS): pandemic, nursing; challenges; risks, articles published in the period from 2019 to 2022 were included in the work. Being called heroes, this struggle must be recorded in the history of nursing, as it was an important class in the pandemic period and continues to be not only in the fight against Covid-19. 19 more also in several areas. Nursing has a very important role that ranges from the identification, analysis of suspicious cases, collection of material for exams, guidance on the importance of social distance in addition to care for patients with a positive diagnosis for Covid-19. Given the above and the obstacles experienced during the Covid-19 pandemic, nurses are able to perform their duties well within health institutions. Recognizing this fact makes it possible to implement strategies and take measures that reduce the negative impacts of the pandemic, bringing recognition and showing the importance of these professionals in health services.